The Influence of Generation X and Y Employees on Modern Cities - Kam, Aygun; Trippner‑Hrabi, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
The employee profile in the business world is becoming increasingly diverse. This change shows that the working population structure of cities has also diversified. The entry of different generation members into business life may mean that they have different perspectives and expectations for the organisations they work for. The main aim of the paper is to investigate the importance of the influence of the characteristics of Generation X and Y employees on professional and urban life. From this perspective, a study was carried out on 235 white‑collar employees working in service, sales and marketing businesses in the private sector in Istanbul in order to investigate the effects of Generation X and Y employee characteristics on working and urban life. The data were obtained in the course of a quantitative study carried out by means of an interview questionnaire using the CAPI (Computer Assisted Personal Interview) technique. According to the literature, the entry of different generation members into business life means that they have different perspectives and expectations for the organisations and cities they work for. However, our research shows the completely opposite view that members of different generations do not have different characteristics and expectations.